2018
DOI: 10.1002/bjs.10853
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis evaluating music interventions for anxiety and pain in surgery

Abstract: BackgroundThis study aimed to evaluate anxiety and pain following perioperative music interventions compared with control conditions in adult patients.MethodsEleven electronic databases were searched for full‐text publications of RCTs investigating the effect of music interventions on anxiety and pain during invasive surgery published between 1 January 1980 and 20 October 2016. Results and data were double‐screened and extracted independently. Random‐effects meta‐analysis was used to calculate effect sizes as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
191
3
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(239 citation statements)
references
References 106 publications
(197 reference statements)
10
191
3
12
Order By: Relevance
“…The result was consistent with that of previous studies. Kühlmann et al and Chi and Young summarized that music chosen by the participants from a preselected list demonstrated positive outcomes because the reaction to music was relatively individualized and dependent on the person's previous experience and culture, so allowing the participants to select their favorite music is encouraged . Therefore, listening to patient‐preferred music shows positive benefits in terms of relieving pain …”
Section: Discussionmentioning
confidence: 99%
“…The result was consistent with that of previous studies. Kühlmann et al and Chi and Young summarized that music chosen by the participants from a preselected list demonstrated positive outcomes because the reaction to music was relatively individualized and dependent on the person's previous experience and culture, so allowing the participants to select their favorite music is encouraged . Therefore, listening to patient‐preferred music shows positive benefits in terms of relieving pain …”
Section: Discussionmentioning
confidence: 99%
“…Studies on the neurochemistry of music point to its influence on factors related to reducing stress and enhancing social bonding (Chanda and Levitin, 2013). A meta-analysis of music therapy studies concluded that it is effective in reducing pain and anxiety (Kühlmann et al, 2018), something which appears to be related to reducing levels of cortisol and ACTH (adrenocorticotropic hormone). Listening to soothing music was found to increase oxytocin levels during post-surgery bed rest (Nilsson, 2009), and Kreutz (2014) found that, compared to dyadic chatting, group singing increased oxytocin levels, as well as significantly enhancing perceived psychological well-being.…”
Section: Mimesis Musical Engagement and Emotional Controlmentioning
confidence: 99%
“…6,21 Music intervention during any type of surgery performed not only reduces anxiety, but also pain and stress levels. 4,22,23 Earlier studies with patients undergoing surgery under general anesthesia that included music intervention intraoperatively or postoperatively, also resulted in a reduction in the anxiety levels. 24,25 The current study showed that all physiological parameters decreased significantly post music therapy (p<0.01).…”
Section: Discussionmentioning
confidence: 99%
“…1,2 World health organization (WHO) has estimated 266-360 million surgical procedures performed annually worldwide. 3,4 Many studies have reported that the dosage level of anesthesia has been increased to reduce the anxiety levels of patients which could result in untoward side effects. 5,6 Visual therapy, journaling, scheduling of pleasant activities, meditation and skills training are few other techniques used to improve the psychological status of a patient.…”
Section: Introductionmentioning
confidence: 99%